2019
DOI: 10.1101/627182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular signatures of selection associated with host-plant differences in Pieris butterflies

Abstract: 20Adaptive traits that enable organisms to conquer novel niches and experience subsequent 21 diversification are ecologically and evolutionarily important. The larvae of Pieris butterflies 22 express nitrile-specifier proteins (NSPs), a key innovation for overcoming the glucosinolate (GLS)-23 myrosinase-based defense system of their Brassicales host-plants. NSPs are a member of the NSP-24 like gene family, which includes the major allergen (MA) protein, a paralog of NSP with a GLS-25 disarming function, and a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Recent experiments have shown dramatic regulatory changes in detoxification pathways following host shifts in plant‐feeding arthropods (Dermauw et al., 2013; Govind et al., 2010; Müller et al., 2017; Yu et al., 2016; Zhang et al., 2017). Additionally, other comparative genomic studies have found similar evidence of positive selection in detoxification genes related to host plant utilization (Simon et al., 2015; Gloss et al, 2019; Okamura et al., 2019). Although the proportion of detoxification proteins under selection from the branch‐site test is high in CPB, these values are relatively low in L. tumamoca and L. peninsularis .…”
Section: Discussionmentioning
confidence: 67%
“…Recent experiments have shown dramatic regulatory changes in detoxification pathways following host shifts in plant‐feeding arthropods (Dermauw et al., 2013; Govind et al., 2010; Müller et al., 2017; Yu et al., 2016; Zhang et al., 2017). Additionally, other comparative genomic studies have found similar evidence of positive selection in detoxification genes related to host plant utilization (Simon et al., 2015; Gloss et al, 2019; Okamura et al., 2019). Although the proportion of detoxification proteins under selection from the branch‐site test is high in CPB, these values are relatively low in L. tumamoca and L. peninsularis .…”
Section: Discussionmentioning
confidence: 67%
“…However, all species had relatively high p N / p S and ω compared with other insect taxa (Heger and Ponting 2007; Rouselle et al. 2016; Okamura et al. 2019; Pinharanda et al.…”
Section: Discussionmentioning
confidence: 89%
“…To assess whether seasonal changes in wing morphology and flight behaviours, we study two polyvoltine butterfly species, Pieris napi (Linnaeus, 1758) and P. rapae (Linnaeus, 1758) (Pieridae: Pierini). These two species are closely-related (Okamura et al, 2019), co-occur in Europe and are ecologically very similar (Tenger-Trolander et al, 2023). They are known to differ in wing size and shape in spring and summer (Fric et al, 2006;Shkurikhin & Oslina, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While P. napi usually flies in habitats such as forest edges and feeds on biennial and perennial plants, P. rapae explores temporary and degraded habitats with ephemeral plants (Ohsaki & Sato, 1999), including agricultural landscapes (Ryan et al, 2019). Seasonal differences in population dynamics driven by climate have also been reported for P. napi and P. rapae (Okamura et al, 2019;von Schmalensee et al, 2023). While P. rapae is more abundant during summer, P. napi has a higher overwintering survival than P. rapae, resulting in higher abundances during the spring (von Schmalensee et al, 2023).…”
Section: Introductionmentioning
confidence: 99%